Exercise, protein metabolism, and muscle growth - Tipton, K. D.; Wolfe, R. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2001)
Exercise has a profound effect on muscle growth, which can occur only if muscle protein synthesis exceeds muscle protein breakdown; there must be a positive muscle protein balance. Resistance exercise improves muscle protein balance, but, in the absence of food intake, the balance remains negative (i.e., catabolic). The response of muscle protein metabolism to a resistance exercise bout lasts for 24-48 hours; thus, the interaction between protein metabolism and any meals consumed in this period will determine the impact of the diet on muscle hypertrophy. Amino acid availability is an important regulator of muscle protein metabolism. The interaction of postexercise metabolic processes and increased amino acid availability maximizes the stimulation of muscle protein synthesis and results in even greater muscle anabolism than when dietary amino acids are not present. Hormones, especially insulin and testosterone, have important roles as regulators of muscle protein synthesis and muscle hypertrophy. Following exercise, insulin has only a permissive role on muscle protein synthesis, but it appears to inhibit the increase in muscle protein breakdown. Ingestion of only small amounts of amino acids, combined with carbohydrates, can transiently increase muscle protein anabolism, but it has yet to be determined if these transient responses translate into an appreciable increase in muscle mass over a prolonged training period.